Influence of fluid inlet–outlet on hydrothermal evaluation for different serpentine mini‐channel heat sink configurations. Issue 8 (31st July 2022) - Al‐Hasani, Hayder Mohammed; Freegah, Basim
Abstract: In the current study, numerical and experimental investigations of the hydrothermal performance of three configurations of a serpentine mini‐channel heat sink (MCHS) were conducted. The outcome of one inlet with two outlets has been studied for two new models, namely, A and B, and compared with the traditional MCHS model. Model A has a central side single inlet, then the channel is directly split and the two outlets are on the other side. In Model B, the single side inlet passes to the other side, and then it splits and the outlets are on the same inlet side. The numerical solution is obtained by using the commercial ANSYS Fluent 2020 R2 under laminar flow conditions. The current study's numerical results were compared and validated with the experimental results of the traditional model. The results reveal that the total performance factor has considerably improved, according to the findings for the model (A and B). The average total hydrothermal performance for Model B is 1.48 and for Model A is 1.53 as compared to the traditional MCHS. However, the temperature distribution, maximum base temperature, Nusselt number, and thermal resistance of Model B are best as compared to Model A.